Age-related longitudinal change in cardiac structure and function in adults at increased cardiovascular risk - Gong, F.F.; Coller, J.M.; McGrady, M.; Boffa, U.; Shiel, L.; Liew, D.; Stewart, S.; Owen, A.J.; Krum, H.; Reid, Christopher; Prior, D.L.; Campbell, D.J. (WILEY PERIODICALS, INC, 2020)
Aim: Heart failure (HF) incidence increases markedly with age. We examined age-associated longitudinal change in cardiac structure and function, and their prediction by age and cardiovascular disease (CVD) risk factors, in a community-based cohort aged ≥60 years at increased CVD risk but without HF.